Effects of Protein Levels and Supplementation of Methyl Group Donor on Nutrient Digestibility and Performance of Broiler Chickens in the Tropics - Ratriyanto , Adi; Indreswari, Rysca; Sunarto, (International Journal of Poultry Science, 2014)
This study was conducted to investigate the effects of protein levels and supplementation of methyl group donors on nutrient digestibility and performance of broiler chickens. Three experimental diets were formulated to have three levels of crude protein (23, 21.5 and 20%). Each protein level was supplemented with methyl group donor (methionine or betaine) and was categorized by: without supplementation (control), with supplementation of 0.14% methionine, 0.14% betaine and combination of 0.14% methionine plus 0.14% betaine. The diets were applied to 540 broiler chickens, which were randomly assigned to 3 x 4 factorial arrangement. Dietary with 21.5 and 20% protein and the supplementation of methyl group donor increased the digestibility of dry matter, crude protein and crude fiber (p